2006
DOI: 10.1088/0029-5515/46/4/s11
|View full text |Cite
|
Sign up to set email alerts
|

Escaping and transport barrier due to ergodic magnetic limiters in tokamaks with reversed magnetic shear

Abstract: Analytical tokamak plasma equilibria, with non-monotonic plasma current profile and perturbed by ergodic magnetic limiters, are described by non-twist conservative maps. Examples are given of concentration of magnetic field lines escaping to the tokamak wall. The robustness of invariant curves on the shearless region is also observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…A least square power fit to the results shows that the percentage deviation varies as N −10 p , where k = 2π/N p . From this analysis, we conclude that the average size of magnetic asymmetries introduced by symplectic discretization in the DIII-D map in natural canonical coordinates is extremely fast, σ scales as k 10 . This means that if we choose sufficiently small k (or sufficiently large N p ), the oscillations in the equilibrium poloidal flux (or the noise in the Hamiltonian) can be made considerably small in the DIII-D.…”
Section: Stochastic Broadening From Toroidal Asymmetries Introduced B...mentioning
confidence: 84%
See 2 more Smart Citations
“…A least square power fit to the results shows that the percentage deviation varies as N −10 p , where k = 2π/N p . From this analysis, we conclude that the average size of magnetic asymmetries introduced by symplectic discretization in the DIII-D map in natural canonical coordinates is extremely fast, σ scales as k 10 . This means that if we choose sufficiently small k (or sufficiently large N p ), the oscillations in the equilibrium poloidal flux (or the noise in the Hamiltonian) can be made considerably small in the DIII-D.…”
Section: Stochastic Broadening From Toroidal Asymmetries Introduced B...mentioning
confidence: 84%
“…The reason for this is that here the new approach is used for the DIII-D, and more details of how the new approach is applied are given, so that if other researchers wish to apply the new approach to the exact magnetic geometries of the ITER [5], the ASDEX UG [6], or other divertor tokamak, they can readily do so. Construction of symplectic mappings for integration of magnetic field lines in tokamaks is an important and active area of present day fusion science research; see [1,[5][6][7][8][9][10][11][12][13][14][15] and [17][18][19][20][21][22][23][24][25][26] in [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent work has shown that the connection lengths are comparable to the electron collisional mean free path for tokamaks with divertors [10]. In our work, we are going to study the patterns produced by the escaping chaotic field line near the tokamak wall [11,12] for an equilibrium with reversed magnetic shear perturbed by an ergodic magnetic limiter. The escaping of the field line is analyzed for a range of control parameters and the connections lengths are calculated and compared to the electron collisional mean free path in order to estimate the relevance of the field line transport.…”
Section: Introductionmentioning
confidence: 98%
“…Our goal in this work is to present a particular solution for this wave Hamiltonian model that prevents the breaking of the RT, even if we add as many waves as we want in the perturbation. This is an important fact since the creation of barriers in Hamiltonian systems has been considered an important subject in several areas of physics especially in plasma confinement in tokamaks [2,7,12,13].…”
mentioning
confidence: 99%